Optimized Parking System Using Internet of Things - Mrs. Qudsia Tahniyath,; Mrs. Anees Fatima,; Mr. Syed Rizwan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This paper describes the complete design and construction of an Arduino-based automatic car parking system that employs Infrared (IR) sensors in an Internet of Things (IOT) environment. The major purpose is to improve the parking process by automatically recognizing the available parking spots and controlling a gate mechanism for vehicle entry and exit. IR sensors are strategically positioned to monitor every parking spot and determine whether a car is present. LEDs visually indicate each spot's occupancy status, providing drivers with real-time feedback. A servo motor is used to run a gate barrier, which opens and closes depending on the availability of parking spots. If an unoccupied spot is found, the gate opens automatically, allowing admission of vehicles; otherwise, it remains closed. Furthermore, the system is designed to be scalable, allowing for quick expansion to accommodate additional parking spots. This method is efficient and cost-effective since it reduces the need for manual supervision while also enhancing space usage. It is especially applicable in urban places or amenities where traditional parking administration is inefficient or unfeasible. This article provides a step toward smarter infrastructure, focusing on automation, convenience, and scalability.
Keywords: Arduino-Uno; Infrared (IR) Sensors; Internet of Things (IOT); Gate mechanism; Scalable